Pharmacokinetics of Tacrolimus during Pregnancy - Zheng, Songmao (2012)
BACKGROUND: Information on the pharmacokinetics of tacrolimus during pregnancy is limited to case reports despite the increasing number of pregnant women being prescribed tacrolimus for immunosuppression. METHODS: Blood, plasma and urine samples were collected over one steady-state dosing interval from women treated with oral tacrolimus during early to late pregnancy (n = 10) and postpartum (n = 5). Total and unbound tacrolimus as well as metabolite concentrations in blood and plasma were assayed by a validated LC/MS/MS method. A mixed effect linear model was used for comparison across gestational age and using postpartum as the reference group. RESULTS: The mean oral clearance (CL/F) based on whole blood tacrolimus concentration was 39% higher during mid- and late-pregnancy compared to postpartum (47.4 ± 12.6 vs. 34.2 ± 14.8 L/h, P < 0.03). Tacrolimus free fraction increased by 91% in plasma (f(P)) and by 100% in blood (f(B)) during pregnancy (P = 0.0007 and 0.002, respectively). Increased f(P) was inversely associated with serum albumin concentration (r = − 0.7, P = 0.003), which decreased by 27% during pregnancy. Pregnancy related changes in f(P) and f(B) contributed significantly to the observed gestational increase in tacrolimus whole blood CL/F (r(2) = 0.36 and 0.47 respectively, P < 0.01). In addition, tacrolimus whole blood CL/F was inversely correlated with both hematocrit and red blood cell counts, suggesting that binding of tacrolimus to erythrocytes restricts its availability for metabolism. Treating physicians increased tacrolimus dosages in study participants during pregnancy by an average of 45% in order to maintain tacrolimus whole blood trough concentrations in the therapeutic range. This led to striking increases in unbound tacrolimus trough concentrations and unbound AUC, by 112% and 173%, respectively during pregnancy (P = 0.02 and 0.03, respectively). CONCLUSIONS: Tacrolimus pharmacokinetics are altered during pregnancy. Dose adjustment to maintain whole blood tacrolimus concentration in the usual therapeutic range during pregnancy increases circulating free drug concentrations, which may impact clinical outcomes.